Dealing with the Past in Security Sector Reform - Mayer-Rieckh, Alexander (SSR Papers, 2013)
Security sector reform (SSR) and transitional justice processes often occur alongside each other in societies emerging from conflict or authoritarian rule, involve many of the same actors, are supported by some of the same partner countries and impact on each other. Yet the relationship between SSR and transitional justice, or â dealing with the pastâ (DwP) as it is also called, remains underexplored and is often marked by ignorance and resistance. While SSR and transitional justice processes can get into each otherâ s way, this paper argues that SSR and DwP are intrinsically linked and can complement each other. SSR can make for better transitional justice and vice versa. Transitional justice needs SSR to prevent a recurrence of abuses, an essential element of justice. SSR can learn from transitional justice not only that it is better to deal with rather than ignore an abusive past but also how to address an abusive legacy in the security sector. The validity of these assumptions is tested in two case studies: the police reform process in Bosnia and Herzegovina after 1995 and the SSR process in Nepal after 2006.